The effect of aging on identification of Mandarin consonants in normal and whisper registers - Xu, Min; Shao, Jing; Ding, Hongwei; Wang, Lan (Frontiers in Psychology, 2022)
Consonant perception in older adults has been widely explored in recent years. However, how aging affects the identification of Mandarin consonants, especially in whispered condition, are under studied. Mandarin consonants and whispering speech have unique features, which may result in different identification difficulties for older adults. The current study investigated older adults’ identification of Mandarin consonants in phonated and whispered conditions in comparison with the performance of younger adults. It was found that in phonated condition, older adults showed the lowest accuracy for affricatives and fricatives owing to their insensitivity to high-frequency information. The lower accuracy of affricatives and plosives was largely attributed to the difficulty in recognizing articulatory places. Identifying aspirated plosives was much more difficult than unaspirated counterparts for older adults. In whispered condition, the recognition of voiced consonants and aspirated-unaspirated distinction became challenging, especially for older adults. Contrary to the expectation, some consonants became easier to be recognized in the whispered condition, i.e., /ph, tɕh, x/. These findings enriched our understanding of how aging affects consonant identification in different languages and less ideal conditions. It also revealed that the listener’s ability, language uniqueness, and characteristics of distorted speech should be all taken into consideration when investigating speech perception in adverse conditions.